(untitled) (Research, Society and Development, 2022)
Mandibular fractures are the most common in children, however with a low incidence because of child anatomy. Among the sites, the condyle is one the most fracture site, being a dilemma to surgeons about your management. The treatment to condyle fracture can be a surgical approach or conservative management. Conservative treatment presents the IMF, appliances, soft diet, and physiotherapy as an option, and these treatments can be applied isolated or associated. Physical Therapy has been a few reported in the literature as isolated therapy, reported as complementing the surgical approach, or after orthodontic/appliances therapy. Promote early mandibular mobility is important to restore function and prevent future complications such as ankylosis. Instruments to perform physiotherapy are expensive and not accessible to the entire population. Therefore, the present study presents a case of a pediatric patient with condyle fracture treated with a soft diet and physiotherapy with wooden spatula.